Institutional Determinants of Student Achievement - Microeconometric Evidence - Susanne Link (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2013)
This volume was prepared by Susanne Link during her stay at the Ludwig-Maximilians-University of Munich and the Department of Human Capital and Innovation of the Ifo Institute of Economic Research. It was accepted as a doctoral thesis by the Economics Departure of the University of Munich in December 2012. The thesis consists of four core chapters, each evaluating the effect of a policy reform. Chapters 2 to 4 provide a contribution to the literature on economics of education and investigate the impact of three educational institutions on student achievement. Chapter 5 evaluates the success of the Federal Expellee Law, which was introduced to improve the economic situation of the expellees after they were forced to leave their homelands in the aftermath of World War II. The econometric analyses are based on different micro data sets and employ micro-econometric methods to identify causal effects.
Keywords: D04; I20; I21; I23; I24; I25; I28; J16; J61; N30; O15; 330; Student achievement; school autonomy; decentralization; developing countries; educational production; international student achievement tests; panel estimation; single-sex schooling; random assignment; peer effects; incentives; higher education; difference-in-differences approach; forced migration; integration policy.; Bildungswesen; Institutionenökonomik; Bildungsniveau; Schätzung; Welt; Deutschland; Südkorea; Flüchtlinge; Kriegsfolgen; Arbeitsmarktpolitik; Arbeitsmarktintegration; Wirkungsanalyse; Deutschland